Characterization of bleaching earth and its performance to palm oil processing - Ismail, Nor Syahira Adila (2017)
This paper study the characterisation of three different type of absorbent which is one of the major tool that will used to predict its performance for palm oil processing. Bleaching earth sample will be collected from Sime Darby research Sdn. Bhd. were characterized by using X-ray Fluorescence (XRF), Inductively Coupled Plasma (ICPOES) and Fourier Transform Infrared Radiation (FTIR). From XRF result, the composition of each component that exist in the absorbent can be determined such as silica, alumina and magnesium. The composition analysis by using ICP-OES showed the ratio between Na2O:CaO of each absorbent where it need to be less than one. Other than that, it also can be used to determine the SiO2:Al2O3 ratio which need to be greater than one and it indicate the suitability for bleaching processing. Actual laboratory test also has been conducted to determine the performance evaluation and confirmed with the prediction from the characterisation. Few analysis have been conducted such as free fatty acid (FFA) value, Peroxide value (PV), colour and bleaching efficiency. Absorbent one show the best result out of all adsorbent by comparing the characteristic and performance. Based on the XRF absorbent contain highest amount of silica, SiO and alumina, Al2O3 which 43.386 and 14.18 compared to the other adsorbent. It shown lowest amount of metal contain in it such as magnesium, ferum and sodium with value of 17.699, 18.984 and 0.244 respectively. Therefore, absorbent I shown the best result compared to the others